7(h+4h)+3=4h+4h+3

Simple and best practice solution for 7(h+4h)+3=4h+4h+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(h+4h)+3=4h+4h+3 equation:


Simplifying
7(h + 4h) + 3 = 4h + 4h + 3

Combine like terms: h + 4h = 5h
7(5h) + 3 = 4h + 4h + 3

Remove parenthesis around (5h)
7 * 5h + 3 = 4h + 4h + 3

Multiply 7 * 5
35h + 3 = 4h + 4h + 3

Reorder the terms:
3 + 35h = 4h + 4h + 3

Reorder the terms:
3 + 35h = 3 + 4h + 4h

Combine like terms: 4h + 4h = 8h
3 + 35h = 3 + 8h

Add '-3' to each side of the equation.
3 + -3 + 35h = 3 + -3 + 8h

Combine like terms: 3 + -3 = 0
0 + 35h = 3 + -3 + 8h
35h = 3 + -3 + 8h

Combine like terms: 3 + -3 = 0
35h = 0 + 8h
35h = 8h

Solving
35h = 8h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-8h' to each side of the equation.
35h + -8h = 8h + -8h

Combine like terms: 35h + -8h = 27h
27h = 8h + -8h

Combine like terms: 8h + -8h = 0
27h = 0

Divide each side by '27'.
h = 0

Simplifying
h = 0

See similar equations:

| X^2+5x=8x+40 | | 5w+6x=15m | | 11W=4730 | | 17q+45q+23=12q+2 | | g(x+h)=-5x-9 | | 34m-4=65 | | g(x+h)g(x)=-5x-9 | | 4(3x+6)=2(x-7) | | 2x-(-5)=17 | | 5s+25=1s+3 | | 16=4x-7x+10 | | -3=4x-5x-2 | | 8sin(3x)=2 | | 27=2x+2x+7 | | 3w+3+3+3w+4=3w+3w+3 | | 10h+5=62 | | 6-2x-x=-18 | | 14-3q=7+6q | | b^2-5a+6=0 | | g(x+h)letg(x)=-5x-9 | | 3b+18=2b+123 | | 7(2p+3)=2(5p+3) | | 7a-b=2a+3b | | 3x+32=5x+8 | | c(x)=1.75x | | 17.4t=87 | | f(x)=x^3*e^2x | | 4(k+3)=3(k+5) | | 10(-3t-2t)+10-2(6t-13)=0 | | x-4(x+3)=-24 | | Tn=5n+17 | | 4g+2+3=2g+5 |

Equations solver categories